In-home medication management by older adults: a modified ethnography study using digital photography walkabouts. (22nd October 2021) - Faisal, Sadaf; Ivo, Jessica; McMillan, Colleen; Grindrod, Kelly; Patel, Tejal
Abstract: Background: Medication mismanagement can lead to non-optimal management of chronic diseases and poor health outcomes. Objective: The purpose of this study was to better understand meanings associated with in-home medication management and storage practices of older adults with chronic diseases. Methods: A modified ethnographic approach using digital photography walkabouts, observation protocols and field notes were used to document in-home medication organisation and storage locations. Thematic analysis was used to generate themes and sub-themes. Results: Data from multiple home visits of 10 participants (mean age = 76 years; 80% females) including 30 photographs, 10 observation protocols and field notes were analysed. The average number of medications used was reported to be 11.1 (range: 5–20). Themes and sub-themes include choice of storage location (sub-themes: impact on medication behaviour, visibility of medications and storage with other items), knowledge regarding appropriate medication storage conditions (sub-themes: impact on safety of patient and impact on stability of medications) and systems to manage in-home medication intake. Discussion: In-home medication management reflects older adults perspectives regarding privacy, medication taking routine, knowledge about safe and effective storage and organisation systems. The lack of knowledge causing inappropriate medication storage not only impacts the stability of medications, but also increases risk of medication errors and safety, ultimately affecting medication intake behaviours.